The role of Pancasila and Citizenship Education Management in developing student character - Dadang Mulyana (Jurnal Pendidikan Indonesia, 2024)
Pancasila and Citizenship education has a strategic role and function in forming good and reliable citizens, but students are still found who do not obey school rules, are undisciplined, cheat and are even late in submitting assignments. This research aims to explore the role of Pancasila and Citizenship education management in shaping and developing student character at the primary and secondary education levels. This research uses a qualitative approach with descriptive methods. The research results show that effective implementation of Pancasila and Citizenship Education Management can contribute positively to the development of student character. Character education programs supported by educational management, involving curriculum planning, teacher training, and periodic evaluations, have proven a significant impact in forming moral, ethical and civic values in students. Good coordination with parents and the community has also been proven to expand the influence of character education outside the school environment. The results of this research provide empirical support for the important role of Pancasila and Citizenship Education Management in producing a generation with strong character, providing a strong foundation for improving and developing character education programs at the primary and secondary education levels.